Науково-практична дискусія стосовно прийняття Закону «Про Президента України»: теорія і практика - Берназюк, Я.; Bernaziuk, Ia. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті узагальнено дискусію стосовно доцільності прийняття закону «Про Президента України». Аналіз відповідної дискусії дозволяє стверджувати, що не є однозначним висновок стосовно доцільності прийняття закону «Про Президента України» та врегулювання на рівні акта парламенту, серед іншого, і процесу правотворчості глави держави. Ідея прийняття закону «Про Президента України» здебільшого не узгоджується з положеннями Конституції України та позицією Конституційного Суду України, які виключають можливість прийняття спеціального закону стосовно розширення або звуження конституційних повноважень глави держави. Крім того, це може призвести до дублювання положень інших законів України. Разом з тим є необхідність визнання нечинним Закону УРСР «Про Президента Української РСР», який втратив актуальність після прийняття Конституції України та суперечить низці її положень. The article presents the main items of the discussion on the expediency of adopting the Law «On the President of Ukraine». Analysis of the conclusions of the discussion suggests that there is a clear opinion on the expediency of adopting the Law «On the President of Ukraine» and regulation at the level of act of Parliament, among other things, the law-making duty of the state head. The idea of the Law «On the President of Ukraine», which is being discussed in academia and among practitioners, are largely inconsistent with the provisions of the Constitution of Ukraine and the opinion of the Constitutional Court of Ukraine, which exclude the possibility of adopting a special law regarding expansion or narrowing of the constitutional powers of the President. In addition, it could lead to duplication of the provisions of other laws of Ukraine, which define the mechanism of realization of the constitutional powers of the President, and to the deregulation of existing in Ukraine system of checks and balances. However, there are grounds to acknowledge invalid the Law of the USSR «On the President of the Ukrainian SSR», which has lost its relevance since the adoption of the Constitution of Ukraine contradicts a number of its provisions. Today especially urgent is the need to amend the first paragraph of Article 106 of the Constitution of Ukraine aimed at securing immediate and detailed powers of the President of Ukraine, not provided for in the Constitution, but directly used and which are essential to perform the functions of the President. The author emphasizes that it is also advisable to put paragraph 31 of Article 106 of the Constitution of Ukraine as follows: «The President of Ukraine exercises other powers determined by the Constitution and laws of Ukraine, aimed at performing the functions set out in Article 102 of the Constitution». This will remove the contradiction between the current version of the regulations and the provisions of Article 106 of the Constitution of Ukraine.
Sсientific Discussion Regarding the Adoption of Law «On the President of Ukraine»: Theory and Practice.
Keywords: конституційне право; Президент України; правовий статус; законтворчість; Constitutional law; President of Ukraine; the legal status; legislation